2013
DOI: 10.3797/scipharm.1211-14
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Key Digestive Enzymes-Related to Diabetes and Hyperlipidemia and Protection of Liver-Kidney Functions by Trigonelline in Diabetic Rats

Abstract: Diabetes is a serious health problem and a source of risk for numerous severe complications such as obesity and hypertension. Treatment of diabetes and its related diseases can be achieved by inhibiting key digestive enzymes related to starch and lipid digestion. The findings revealed that the administration of trigonelline to surviving diabetic rats helped to protect the pancreas β-cells from death and damage. Additionally, the supplement of trigonelline to surviving diabetic rats significantly decreased inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 17 publications
(23 reference statements)
5
31
0
Order By: Relevance
“…Similar effects were reported for 3,5-T 2 when used as a pharmacological agent to prevent insulin resistance forced by a high-fat diet [5]. Further animal studies [27,35,36] confirmed the antidiabetic effect of both trigonelline and 3,5-T 2 , revealing protective effects on impaired kidney function and structure, which represents a severe sequelae of type 2 diabetes mellitus. Taken together, 3,5-T 2 and trigonelline were linked to glucose metabolism, exhibiting the potential to improve glucose homeostasis in the case of diminished insulin sensitivity.…”
Section: Discussionsupporting
confidence: 62%
“…Similar effects were reported for 3,5-T 2 when used as a pharmacological agent to prevent insulin resistance forced by a high-fat diet [5]. Further animal studies [27,35,36] confirmed the antidiabetic effect of both trigonelline and 3,5-T 2 , revealing protective effects on impaired kidney function and structure, which represents a severe sequelae of type 2 diabetes mellitus. Taken together, 3,5-T 2 and trigonelline were linked to glucose metabolism, exhibiting the potential to improve glucose homeostasis in the case of diminished insulin sensitivity.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, insulin, HOMA‐IR and altered lipid profile were corrected. These results match previous findings in diabetic and insulin‐resistant rats . The current work verified the involvement of the crucial insulin signalling pathway in the antihyperglycemic effect of TRG.…”
Section: Discussionsupporting
confidence: 92%
“…7 During the roasting process of coffee beans, trigonelline changes into N-methylpyridinium ( Figure 17.3(B)) and nicotinic acid ( Figure 17.3(C)) as its major products, which makes it a useful index of the degree of roasting. 10 In addition, the urinary concentrations of trigonelline and its thermal product Nmethylpyridinium of coffee drinkers are higher than those of noncoffee drinkers, which indicates that trigonelline and N-methylpyridinium may have potential as dietary biomarkers that could be used as analytical probes to control compliance in human intervention studies on coffee. It has been revealed in recent studies that the administration of trigonelline allows diabetic rats to avoid diabetes-related organ damage and live longer, which can make it a potentially strong candidate for industrial application as a pharmacological agent for the treatment of hyperglycemia, hyperlipidemia, and liver/kidney dysfunctions.…”
Section: Trigonellinementioning
confidence: 99%